2022
DOI: 10.1111/acer.14809
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐ and provider‐level factors that underlie alcohol use disorder treatment offer and acceptance in veterans with cirrhosis

Abstract: Background Untreated alcohol use disorder (AUD) is associated with poor cirrhosis outcomes. We evaluated factors associated with AUD treatment discussions and initiation in the Veterans Health Administration. Methods Chart reviews were conducted for veterans with International Classification of Diseases codes for both cirrhosis and AUD who were receiving care at one of three large medical centers in 2020. Factors associated with a 1‐year offer of AUD treatment and its acceptance were assessed using regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…We found that many times patients declined offers for AUD treatment in a chart review study. 6 Likewise, our non-VA study found strong evidence of provider stigma in these conversations and their notes, which may translate into patient decline. 5 These findings emphasize the need for future work toward increasing AUD-related care, which starts with capturing data from all ends of the patient, caregiver, system, and societal spectrum.…”
mentioning
confidence: 66%
“…We found that many times patients declined offers for AUD treatment in a chart review study. 6 Likewise, our non-VA study found strong evidence of provider stigma in these conversations and their notes, which may translate into patient decline. 5 These findings emphasize the need for future work toward increasing AUD-related care, which starts with capturing data from all ends of the patient, caregiver, system, and societal spectrum.…”
mentioning
confidence: 66%
“… 25 Another retrospective review also found that only 64% of cirrhosis patients were offered outpatient AUD treatment. 26 Factors that impede the implementation of SBIRT include gaps in knowledge or comfort about aspects of managing AUD, such as pharmacotherapy, as well as insufficient healthcare resources and system limitations. 24 , 26 , 27 Most of the SBIRT in our study was started by social workers and addictions counsellors, which further highlights the importance of a multidisciplinary approach to AUD and ALD.…”
Section: Discussionmentioning
confidence: 99%